Efficacy and safety of tranexamic acid combined with low molecular weight heparin versus fondaparinux sodium following total knee arthroplasty: a retrospective cohort study - Haibier, Abuduwupuer; Pan, Miying; Anwar, Dilxat; Ma, Pengcheng (Frontiers in Pharmacology, 2025)
BackgroundLow molecular weight heparin (LMWH) and fondaparinux (FPX) are commonly used to prevent deep vein thrombosis (DVT) following total knee arthroplasty (TKA). This study aimed to compare the efficacy and safety of tranexamic acid (TXA) combined with LMWH versus TXA combined with FPX in preventing DVT among TKA patients.MethodsA retrospective cohort study was conducted involving patients who underwent unilateral TKA at our institution between January 2020 and December 2023. Patients were divided into two groups based on their anticoagulation regimen: the TXA + LMWH group (n = 150) and the TXA + FPX group (n = 130). Perioperative indicators (blood loss, hospital stay, operative time, transfusion rate, transfusion volume, and total hospitalization costs), complications (DVT, muscular calf vein thrombosis [MCVT], surgical site infection, pulmonary thromboembolism, and postoperative hematoma), adverse reactions, coagulation parameters (D-dimer, prothrombin activity, INR, fibrinogen), and routine blood parameters (platelet count, hemoglobin, hematocrit) were compared between groups.ResultsNo significant differences were observed between groups in perioperative blood loss, operative time, hospital stay, transfusion rate, or volume (P > 0.05). While most preoperative baseline characteristics were comparable, the TXA + FPX group had significantly better baseline renal function (P < 0.05)0. On postoperative days 1 and 5, levels of D-dimer, prothrombin activity, INR, and fibrinogen were significantly lower in the TXA + LMWH group compared to the TXA + FPX group (P < 0.05). Total hospitalization costs were significantly lower in the TXA + LMWH group (P < 0.05). Additionally, the TXA + LMWH group exhibited a significantly lower overall complication rate (28.00% vs. 47.69%, P < 0.05) and lower incidence of MCVT (20.67% vs. 32.31%, P < 0.05). No significant differences were found in rates of DVT, surgical site infection, or postoperative hematoma (P > 0.05). No severe complications, such as pulmonary thromboembolism, acute renal failure, seizures, or death, occurred in either group.ConclusionTXA combined with LMWH demonstrates significant advantages over TXA combined with FPX in reducing overall complications, particularly MCVT, and lowering hospitalization costs, with favorable improvements in coagulation parameters. Both regimens showed comparable efficacy in managing perioperative blood loss, operative time, hospital stay, and transfusion requirements in TKA patients. Given the retrospective design and limited sample size, further validation through high-quality, large-scale prospective studies is warranted.